Conceptual problems with disembodied cognition in learning environment(s) and the alternative of embodied creativity - Briedis, Mindaugas; Navarro, Mariano (Creativity Studies, 2024)
The article is motivated by today’s practical realities and theoretical transformations that have affected education on a major scale. The shift from in-person to online classrooms at the beginning of the pandemic brought forward a series of issues related to embodied conditioning for creative strategies in the learning process. After presenting the shortcomings of the disembodied approach to education, we emphasize the role of the embodied (somatic, motoric, affective) aspects of education and discuss the embodied skills of creativity in a variety of learning environments. While so called embodied creativity became a fast-developing field due to mostly quantitative experiments in teaching-learning environments, it still lacks some conceptual clarification, especially in relation to its genesis in the paradigm of embodied cognition. Hence the main goal of this conceptual article is to extend, through the method of theory adaptation, the existing body of research on embodied cognition in academic environments to show how the embodied teaching and learning paradigm presents embodied creativity methods as an alternative to the disembodied approach to education and how technological environments provide an opportunity for such purposes.